Biocatalytic production of chitosan polymers from shrimp shells, using a recombinant enzyme produced by pichia pastoris - Aguila, Eduardo M.; Gomes, Laidson P.; Andrade, Cristina T.; Silva, Joab T.; Paschoalin, Vânia M. (Scientific Research Publishing, 2012)
Chitosan has a unique chemical structure with high charge density, reactive hydroxyl and amino groups, and extensive hydrogen bonding. Chitin deacetylase (EC 3.5.1.41) catalyzes the hydrolysis of the N-acetamido groups of N-acetyl-D-glucosamine residues in chitin, converting it to chitosan and releasing acetate. The entire ORF of the CDA2 gene encoding one of the two isoforms of chitin deacetylase from Saccharomyces cerevisiae was cloned in Pichia pastoris. The Tg (Cda2-6xHis)p was expressed at high levels as a soluble intracellular protein after induction of the recombinant yeast culture with methanol, and purified using nickel-nitrilotriacetic acid chelate affinity chromatography, resulting in a protein preparation with a purity of >98% and an overall yield of 79%. Chitin deacetylase activity was measured by a colorimetric method based on the O-phthalaldehyde reagent, which detects primary amines remaining in chitinous substrate after acetate release. The recombinant enzyme could deacetylate chitin, chitobiose, chitotriose and chitotetraose, with an optimum temperature of 50°C and pH 8.0, determined using oligochitosaccharides as the substrates. The recombinant protein was also able to deacetylate its solid natural substrate, shrimp chitin, to a limited extent, producing chitosan with a degree of acetylation (DA) of 89% as determined by Fourier transform infrared spectroscopy. The degree of deacetylation was increased by pre-hydrolysis of crystalline shrimp chitin by chitinases, which increased the deacetylation ratio triggered by chitin deacetylase, producing chito-oligosaccharides with a degree of acetylation of 33%. The results described here open the possibility to use the rCda2p, combined with chitinases, for biocatalytic conversion of chitin to chitosan with controlled degrees of deacetylation. We show herein that the crystalline chitin form can be cleanly produced in virtually quantitative yield if a combined and sequential enzyme treatment is performed.
Keywords: Chitin Deacetylase; Chitosan; Chitin; Pichia Pastoris; Deacetylation Degree